Obesity Prevalence, Associated Factors and Complications among Adult Population Attending Family Medicine Clinic in Hatta Hospital, United Arab Emirates - Ayesha Rashid; Uzma Farheen; Zahid Nabi Qureshi; Muhammad Ejaz (Liaquat National Journal of Primary Care)
Background: The United Arab Emirates (UAE) has experienced rapid economic growth in the last few decades, resulting in swift urbanization and an influx of foreign labor. This has facilitated an advanced, yet sedentary lifestyle characterized by increased reliance on technology, unhealthy dietary habits, and a reduction in physical activity levels. These factors significantly contributed to the rise in the prevalence of obesity. Objective: To determine the prevalence of obesity, it’s associated factors, and complications among adults presenting to the primary care clinic at Hatta Hospital, located in the Hatta area UAE. Materials and Methods: This cross-sectional study enrolled adult Emirati patients aged between 18-55 year. The study duration was from January 2022 to August 2022 Body Mass Index (BMI) was categorized based on the World Health Organization’s threshold. Patients’ socio-demographic and clinical data was obtained and recorded. Results: A total of 600 Emirati patients were included in this study, with a median age of 33 (IQR=25-45) years. Gender distribution was kept almost equal with 50.5% male and 49.5% female participants. The median BMI among the participants was 28.2 (IQR=24.3- 32.5) kg/m2 . The prevalence of underweight, normal weight, overweight, and obesity was found as 4.3%, 23.5%, 33.7% and 38.5% respectively. After adjusting the co-variants in the multivariable model, lower education levels were found to be significantly associated with higher odds of obesity. Conversely, being single and adhering to a healthy lifestyle was associated with lower odds of obesity in the multivariable model. Conclusion: The present study identified that 38.5% of the adult population attending Hatta Hospital family medicine clinics were obese and 33.7% were overweight. Conclusively, 72.2% of the adult population of the Hatta area have a BMI above normal, indicating a very high prevalence of obesity and overweight cases. Furthermore, a significant association of obesity was found with lower education levels, being married, having unhealthy dietary habits, and insufficient physical activity